Heterophoria, fusional amplitudes and stereoacuity in school aged children - Lança, Carla Costa (2015)
The stability of binocular vision depends on good fusional amplitudes and its measurements provide information about the patient’s ability to cope with a deviation. However, weak correlations between fusional amplitudes and angle of deviation have been reported in the literature. There are no uniform normative values of fusional amplitudes, even though standards for vergence have been established since 1940s. Aims: 1) Determine the prevalence of heterephoria; 2) Determine the relationship between heterophoria, fusional amplitudes and stereoacuity in children.